Study on surface discharge characteristics and design method of large size oil-paper insulation of electrical transformer. Issue 1 (1st October 2022) - Zhang, Shuqi; Yu, Xinru; Wu, Chao; Yang, Lijun; Cheng, Huanchao; Deng, Junyu
Abstract: When partial discharge occurs in the power transformer, the arc can further develop on the oil-paper interface between high and low potentials, and then form a path, resulting in large-area flashover. This will lead to a wide range of insulation damage, insulation failure, equipment shutdown and even large-scale economic losses. For the insulation damage caused by surface discharge of oil paper insulation, relevant scientific research institutions have carried out a large number of experimental studies. However, limited by the test conditions, the research focuses on the small-size model below 50mm, and mostly adopts the test device of uneven electric field. The research on the "large-size" of the same scale inside the transformer is still blank. In this study, an oil-paper insulation surface discharge test platform with a large size of 50-150mm is built, the electric field conditions at the oil paper interface during the operation of transformers in engineering are simulated, and the surface discharge test of insulating paperboard is carried out by taking the same sample processing means as the engineering. Combined with the test results, a typical design optimization case of setting along surface corner ring to improve the allowable value of along surface discharge field and enhance along surface insulation margin is proposed. It lays a foundation for enriching the transformer oil-paper insulation design parameter system and improving the transformer oil paper insulation performance and operation reliability.